2022
DOI: 10.21134/rpcna.2022.09.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Training in children with attention deficit hyperactivity disorder: A systematic review

Abstract: Working memory training may help children with attention deficit hyperactivity disorder (ADHD), but robust evidence from systematic reviews is lacking. Children with poor Working memory ability struggle with academic and cognitive work compared to similar-aged peers without working memory deficits. Besides, working memory is correlated with inattention and disorganization in those with ADHD. The aim of this systematic review was to assess the effect of working memory training on symptoms and behaviors of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…This is a strategy that complements the many existing strategies for systematic literature review. In addition to offering consistent and easy-to-interpret results; also, it has been successfully applied in important literature reviews [54], [109], [110].…”
Section: Discussionmentioning
confidence: 99%
“…This is a strategy that complements the many existing strategies for systematic literature review. In addition to offering consistent and easy-to-interpret results; also, it has been successfully applied in important literature reviews [54], [109], [110].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has highlighted the importance of individualized memory training programs tailored to the unique needs of each student (Koyama et al, 2020;Landínez-Martínez et al, 2022). This approach involves identifying specific memory deficits that may be the student's learning and developing targeted strategies to address those deficits (Melby- Lervåg and Hulme, 2013).…”
Section: Relation To Prior Studiesmentioning
confidence: 99%
“…This approach involves identifying specific memory deficits that may be the student's learning and developing targeted strategies to address those deficits (Melby- Lervåg and Hulme, 2013). For instance, Landínez-Martínez et al (2022) found that a personalized working memory training program significantly improved memory performance in children with ADHD. Similarly, Koyama et al (2020) discovered that individualized cognitive training significantly improved working memory in children with developmental dyscalculia.…”
Section: Relation To Prior Studiesmentioning
confidence: 99%